Pembuatan Aplikasi Penentuan Jalur Terpendek Pendistribusian Solar dengan Metode Algoritma Dijkstra Berbasis Web Pada CV. Mega Lestari - Oktaviyani, Tri; Jusak, Jusak; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV. Mega Lestari is a company engaged as service providers to transport diesel fuel manifold to companies, which located at Jl. Tropodo Asri Blok F 31 Sidoarjo. CV. Mega Lestari still does not have technology that can help in running the business of the company, especially in terms of the distribution of goods. The process resulted in delays in the distribution of diesel fuel is often reduced profits. Difficult to estimate the distance and time of the place of destination becomes an obstacle for the company, coupled with drivers who are not familiar with the road. Based on the above, the solution to the problems created for the application of fuel determination of shortest paths distribution method dijkstra algorithm on a web-based CV. Mega Lestari. With this application is expected to help the company runs the business. Applications that have been built in the preparation of this thesis is the application making the determination of the shortest path to the method of distribution of solar dijkstra algorithm on a web-based CV. Mega Lestari. This application can determine the shortest path and estimate the distance and time to the distribution of destination.